2011
DOI: 10.1088/0963-0252/20/3/035017
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy and angular distributions onto polymer surfaces delivered by dielectric barrier discharge filaments in air: I. Flat surfaces

Abstract: In atmospheric pressure discharges, ion energies are typically thought to be thermal with values dominantly <1 eV. In the heads of filaments in dielectric barrier discharges (DBDs), electric fields can exceed 200 kV cm −1 when the filament is far from a surface. As the filament approaches and intersects a dielectric surface, much of the applied potential is compressed into the voltage drop across the head of the filament due to the high conductivity of the trailing plasma channel. When the filament strikes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 17 publications
9
46
0
Order By: Relevance
“…Plasma catalysis can be realized by introducing dielectric packing beads (coated with catalyst material) in the discharge gap, forming a packed bed dielectric barrier discharge (PB-DBD) reactor. The DBD generally occurs in a filamentary mode by applying a high driving voltage [10][11][12][13][14], which induces a very fast ionization avalanche, propagating from powered electrode to grounded electrode, i.e., a so-called streamer [12,13,[15][16][17][18][19]. Each streamer starts when the driving voltage passes a certain threshold, and will further polarize the dielectric surface [20].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma catalysis can be realized by introducing dielectric packing beads (coated with catalyst material) in the discharge gap, forming a packed bed dielectric barrier discharge (PB-DBD) reactor. The DBD generally occurs in a filamentary mode by applying a high driving voltage [10][11][12][13][14], which induces a very fast ionization avalanche, propagating from powered electrode to grounded electrode, i.e., a so-called streamer [12,13,[15][16][17][18][19]. Each streamer starts when the driving voltage passes a certain threshold, and will further polarize the dielectric surface [20].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complexity of the plasma processes created by DBDs, mathematical modelling and numerical simulations are essential tools used to increase our fundamental understanding of the subject [23][24][25][26][27]. Research on local discharge characteristics mainly focuses on the space-time evolution of particles (e.g., excitation and ionization by an electron of a neutral particle, recombination of electrons and ions, and electron thermal and non-thermal attachment and detachment processes), electron mean energy profile, and photo-ionization [28].…”
Section: Introductionmentioning
confidence: 99%
“…This research cannot be easily realized through experimental observation but must be conducted via theoretical analysis. With the advent of more powerful computers and more sophisticated algorithms, numerical modelling has been increasingly employed and will continue to benefit the investigation of non-equilibrium plasma caused by gas discharge [23][24][25][26]28,29].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the DBD plasmas and the use of DBD plasmas in technological devices, three basic models are usually employed: fluid-hydrodynamic model, particle-in-cell/Monte Carlo collision (PIC/MCC) model and hybrid models [5,[15][16][17][18][19][20][21][22]. Fluid models have been developed both for low and high pressure discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid models have been developed both for low and high pressure discharges. Natalia et al reported a multi-fluid hydrodynamics simulation to investigate the ion energy and angular distributions incident on dielectric flat surfaces resulting from the intersection of DBD filaments sustained in atmospheric pressure air [16]. PIC/MCC method provides the most detailed information on the properties (e.g., velocity distributions) of the electrons, ions and atoms [19,20].…”
Section: Introductionmentioning
confidence: 99%